Writing the world : understanding William Stafford - Kitchen, Judith (Oregon State University Press, 1999)
"An excellent introduction for readers coming to William Stafford for the first time and an overview of the work for the many readers already familiar with his poetry, Writing the World offers the best single guide to one of the most respected and celebrated poets of our time."--Jacket.